Relationships between the spectral characteristics of dissolved organic matter and river ecological health indicators: A case study in the Shichuan River basin on a typical semi-arid and semi-humid region of China - Daoping Xi; En Hu; Ming Li; Jian Gao (Ecological Indicators)
The spectral characteristics of dissolved organic matter (DOM) in rivers are considered as potential indicators of river health status. In this study, relationships between DOM spectral properties and river ecological health indicators in Shichuan River, such as total nitrogen (TN), total phosphorus (TP), chlorophyll-a (Chl-a) content, diversity of macrobenthic invertebrates, water quality index (WQI), and trophic level index (TLI), etc., were investigated. According to the WQI values, the water quality of the Ju River and Taoqupo Reservoir was generally better than that of other river sections, while the Qinghe and the mainstream sections performed the worst. The fluorescence index (FI) and WQI reflects that the mainstream of the Shichuan River bears a significant amount of sewage input. Besides, FI showed a significant positive correlation with nitrate nitrogen (NO3−-N), TN, TP, Chl-a, and TLI, while a significant negative correlation with WQI. The specific ultraviolet absorbance of 254 nm (SUVA254) had a positive correlation with TLI. Indeed, the UVC humic-like component (C1) showed a significant positive correlation with the macroinvertebrates diversity. The humification index (HIX) was significantly negatively correlated with sediment pollution index. Our results suggested that DOM fluorescence characteristics had the potential to be developed as a convenient method for assessing aquatic ecological health.